KOMPETENSI KEPRIBADIAN GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBINA AKHLAK PESERTA DIDIK DI SEKOLAH MENENGAH PERTAMA NU HIDAYATUL MUBTADI-IEN KECAMATAN TUNGKAL JAYA - Hasibuan, Neni Iswanti; Yunus, Abdullah; Idarianty (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the personality competence of Islamic Religious Education teachers in fostering the noble character of students at Nu Hidayatul Mubtadi-Ien Junior High School, Tungkal Jaya District, Musi Banyuasin Regency. The background of this research is based on the moral problems found among students, such as lack of discipline, low respect toward teachers, and weak obedience to school regulations. These conditions require the active role of teachers in guiding and developing students’ moral behavior through strong personality competence. This study aims to describe the personality competence of Islamic Religious Education teachers, explain the process of fostering noble character among students, and analyze the efforts carried out by teachers in moral development activities. This research employed a qualitative descriptive method using pedagogical, psychological, managerial, and theological approaches. Data were collected through observation, interviews, and documentation techniques. The findings reveal that the personality competence of Islamic Religious Education teachers has an important role in shaping students’ noble character through exemplary attitudes, discipline, motivation, religious habituation, and continuous guidance. Teachers also implemented moral development programs such as congregational prayer activities, greeting culture, cleanliness awareness, honesty, discipline, and respect toward teachers, parents, and fellow students. The study concludes that the personality competence of Islamic Religious Education teachers significantly contributes to the development of students’ noble character and supports the achievement of educational objectives based on Islamic values.